Iron Folate Consumption, Energy and Iron Adequacy Level Associated with Prevalence of Anaemia among Pregnant Women in Jember - Wahyu Setyaningsih; Luh Seri Ani; Ni Wayan Arya Utami (Public Health and Preventive Medicine Archive, 2015)
Background and purpose: Anaemia among pregnant women is still being a public health problem in Indonesia. This study aimed to determine association between iron folate consumption, energy and iron adequacy level with prevalence of anaemia among pregnant women. Methods: This was a cross-sectional study conducted in eight community health centers in Jember, East Java with 128 pregnant women selected using stratified random sampling from pregnant women’s cohort in each primary health center. Data were collected from interviews using semi quantitative food frequency questionnaire, chronic energy deficiency status by measuring the middle upper arm circumference (MUAC), and data of haemoglobin levels with Easy Touch GCHb (Bioptic Technology Inc., China). Data were analysed bivariate by chi-square and multivariate by logistic regression. Results: This study found that the prevalence of anaemia among pregnant women in Jember was 60.16% (95%CI: 51.76-68.56). Multivariate analysis resulted that variables which significantly reduce risk of anaemia among pregnant women were: household income (adjusted OR=0.09; 95%CI: 0.03-0.51), iron folate consumption (adjusted OR=0.16; 95%CI: 0.04-0.69), adequacy of energy (adjusted OR=0.06; 95%CI: 0.01-0.33), and iron adequacy level (adjusted OR=0.11; 95%CI: 0.01-0.90). Conclusion: Household income, intake food with high energy and iron, and also iron folate consumption significantly reduced the risk of anaemia among pregnant women.